COMPARATIVE EFFECTIVENESS BETWEEN HEEL RAISE EXERCISES AND RESISTANCE BAND EXERCISES ON FUNCTIONAL ABILITY IN ATHLETES WITH ANKLE INJURIES - Samuel Frandito Pramaditya T; Mianti Nurrizky Sutejo; Ragil Aidil Fitriasari Addini; Nana Noviada Kwartawaty (Physiotherapy and Physical Rehabilitation Journal, 2024)
Background: Ankle injuries are among the most common sports injuries, affecting athletes with symptoms such as pain, swelling, joint instability, muscle weakness, and reduced functional activity. Effective interventions, such as heel raise exercises and resistance band exercises, are crucial for managing these injuries.. Objective: This study aims to compare the effects of heel raise exercises and resistance b and exercises on improving functional ability in athletes with ankle injuries. Method: A quasi-experimental design with a pre-test and post-test two-group approach was used. The study sample consisted of 22 athletes from Nafas Bintang Barat FC, with 11 athletes assigned to the heel raise exercise group (Group I) and 11 athletes assigned to the resistance band exercise group (Group II). Participants were selected using purposive sampling. Functional ability was assessed using the Foot and Ankle Ability Measure (FAAM).. Results: The Paired Sample Test revealed significant improvements in functional ability within both groups, with p-values of 0.000 for Group I and 0.000 for Group II, indicating that both interventions were effective. However, the Independent Sample Test showed no significant difference between the two groups, with an average difference of 0,1816 and a p-value of 0.131, suggesting that there is no significant difference in effectiveness between heel raiseexercises and resistance band exercises.. Conclusion: Both heel raise exercises and resistance band exercises effectively improve functional ability in athletes with ankle injuries. However, there is no significant difference in effectiveness between the two exercise modalities.